Distribution and diversity of begomoviruses in tomato and sweet pepper plants in Costa Rica - Barboza Vargas, Natalia María (2017)
Begomoviruses (genus Begomovirus, family Geminiviridae) have emerged as important plant pathogens in tropical and subtropical regions worldwide. Although these viruses were reported during the 1970s in Costa Rica, they are still poorly known. Therefore, the objective of this study was to analyse the diversity and distribution of begomoviruses in commercial tomato and sweet pepper fields from different agricultural production systems of the major growing regions of Costa Rica. A total of 651 plants were randomly sampled from greenhouses and open field crops during 2011 and 2012 in three different geographical locations. The bipartite begomoviruses Tomato yellow mottle virus, Tomato leaf curl Sinaloa virus and Pepper golden mosaic virus, and the monopartite begomovirus Tomato yellow leaf curl virus were detected in the collected samples. The complete genome of isolates from each species was cloned and sequenced. The frequency of detection of these four begomoviruses in the analysed samples ranged from 0 to 9%, the presence, and the prevalent virus varied largely according to the geographical location, the host (tomato and pepper), and the production system (greenhouses or open fields). An association between geographical region and begomovirus species was observed suggesting that in Costa Rica the heterogeneity on climate, topography and agricultural system might influence the distribution of begomovirus species in the country. A broader survey needs to be conducted to confirm it, although these preliminary results may contribute to the management of begomoviruses in Costa Rica.